Myocardial Storage, Inflammation, and Cardiac Phenotype in Fabry Disease After One Year of Enzyme Replacement Therapy - Sabrina Nordin; Rebecca Kozor; Ravi Vijapurapu; João B. Augusto; Kristopher Knott; Gabriella Captur; Thomas A. Treibel; Uma Ramaswami; Michel Tchan; Tarekegn Geberhiwot; Richard P. Steeds; Derralynn Hughes; et al. (2019)
Background: Cardiac response to enzyme replacement therapy (ERT) in Fabry disease is typically assessed by measuring left ventricular mass index using echocardiography or cardiovascular magnetic resonance, but neither quantifies myocardial biology. Low native T1 in Fabry disease represents sphingolipid accumulation; late gadolinium enhancement with high T2 and troponin elevation reflects inflammation. We evaluated the effect of ERT on myocardial storage, inflammation, and hypertrophy. Methods: Twenty patients starting ERT (60% left ventricular hypertrophy–positive) were compared with 18 patients with early disease and 18 with advanced disease over 1 year at 3 centers. Cardiovascular magnetic resonance (left ventricular mass index, T1, T2, global longitudinal strain, and late gadolinium enhancement) and biomarkers (high-sensitive troponin-T and NT-proBNP [N-terminal Pro-B-type natriuretic peptide]) at baseline (pre-ERT) and 12 months were performed. Early disease controls were stable, treatment-naïve patients (mainly left ventricular hypertrophy–negative); advanced disease controls were stable, established ERT patients (mainly left ventricular hypertrophy–positive). Results: Over 1 year, early disease controls increased maximum wall thickness and left ventricular mass index (9.8±2.7 versus 10.2±2.6 mm; P =0.010; 65±15 versus 67±16 g/m 2 ; P =0.005) and native T1 fell (981±58 versus 959±61 ms; P =0.002). Advanced disease controls increased T2 in the late gadolinium enhancement area (57±6 versus 60±7 ms; P =0.023) with worsening global longitudinal strain (−13.2±3.4 versus −12.1±4.8; P =0.039). Newly treated patients had a small reduction in maximum wall thickness (14.8±5.9 versus 14.4±5.7 mm; P =0.028), stable left ventricular mass index (93±42 versus 92±40 g/m 2 ; P =0.186) and a reduction in T1 lowering (917±49 versus 931±54 ms; P =0.017). Conclusions: Fabry myocardial phenotype development is different at different disease stages. After 1 year of ERT initiation, left ventricular hypertrophy–positive patients have a detectable, small reduction in left ventricular mass and storage.